UZBEK NATIONAL DANCE ART AND ITS HISTORICAL STAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article focuses on The Art of Dance, which is the Pearl of Uzbek national art. The Art of Dance is analyzed in details from the earliest periods of human history in labor processes, the development in connection with the household life of the people, as a result of long historical progress, the art of dance is bleached and artistically enriched.